Facilely solution-processed ZnO + Cs2CO3 for robust electron injection in ultraviolet organic light-emitting diode with inverted architecture. (November 2020) - Xu, Kai; Li, Dongliang; Yuan, Yongfang; Xu, Jiwen; Wang, Hua; Wang, Lihui; Lu, Zongliu; Liu, Liming; Lin, Zhidong; Zhang, Xiaowen
Highlights: Solution-processed ZnO + Cs2 CO3 composite electron injection layer is investigated. ZnO + Cs2 CO3 features superior film morphology and exceptional electronic properties. ZnO + Cs2 CO3 behaves robust electron injection. Inverted ultraviolet OLED is demonstrated with solution-processed ZnO + Cs2 CO3 . The mechanism of ZnO + Cs2 CO3 promotes device performance is systematically clarified. Abstract: Electron injection governs electro-optic performance of organic light-emitting diodes (OLEDs) with intractable inverted architecture. Solution process with low cost and scalable manufacturing drives a lab-to-fab journey of electron injection layer (EIL) in OLEDs. Herein, a facilely solution-processed composite EIL of ZnO + Cs2 CO3 with robust electron injection has been explored for constructing ultraviolet OLED with inverted architecture. Using 3-(4-biphenyl)-4-phenyl-5- tert -butylphenyl-1, 2, 4-triazole as emitter, attractive short-wavelength emission of 380 nm and full-width at half-maximum of 37 nm are demonstrated in the inverted ultraviolet OLED. It achieves maximum radiance of 2.42 mW/cm 2 and external quantum efficiency of 0.85% with improved operation durability, which are superior or comparable to the corresponding references using single EILs of Cs2 CO3, ZnO and LiF, or double-stacked EIL of ZnO/Cs2 CO3 . X-ray photoelectron spectroscopy analysis clarifies that the Cs2 CO3, ZnO and ZnO + Cs2 CO3 exhibit exceptional electronic properties. The current-voltage characteristics and impedance spectroscopy analysis of electron-only cells confirm that ZnO + Cs2 CO3 behaves robust electron injection and accounts for excellent device performance. Our results pave an alternative approach for advancing ultraviolet OLED with inverted architecture and facile solution process.